Noun Phrase in Bahasa Indonesia - Ningsih, Rahmi Yulia; Wiharja, Chandra Kurniawan (Bina Nusantara University, 2017)
This article contained research about the analysis of the text of Bahasa Indonesia speech with the Systemic Functional Linguistic approach (LFS). The aim of this article was identifying elements of forming noun phrases as the participants which represented processes in clauses, functions, as well as the distribution of its position in the clause. The research method used was qualitative research with the method of data analysis in the form of 60 clauses through the approach of LFS. The 60 clauses data were taken from the text of the speech of UNJ Rector, which was then analyzed into 100 phrases in the noun. According to the LFS method, it finds that the noun phrase is formed by elements of the noun classes. From the 100 noun phrases analyzed, there are 100 nouns that have different functions in each process. There are 86 nouns represent the material process, 5 nouns represent the relational process, 4 nouns represent the verbal process, 3 nouns represent mental processes, and 2 nouns represent the existential process. The study also finds that in the form of the lexicon, the same noun with the different distribution of its position will result in different functions in the representation process.